In vitro degradation of betaine by ruminal microbes - C.A. Löest; C.K. Armendariz; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2000)
An in vitro study was conducted to evaluate the degradation of betaine sources by rumen microbes. Five sources of betaine (anhydrous betaine, betaine-HCl, feed-grade betaine, lipidcoated betaine, and concentrated separator byproduct) were incubated in rumen fluid collected from steers fed grain- or forage-based diets. In vitro degradation of betaine was slower with the high roughage diet than the grain diet. Betaine from concentrated separator by-product was degraded most rapidly, but no large differences occurred among the other four sources. The disappearance of betaine from lipid-coated product indicates that it did not resist ruminal degradation. Although betaine from all sources was degraded, some still remained after 24 hours of incubation, suggesting that some betaine may bypass the rumen.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Rumen; Betaine; Degradation